PROBLEMATIKA KEPEMIMPINAN PENDIDIKAN ISLAM TRADISIONAL DAN MODERN DI ERA MILENIAL - Asrofi, Moh.; Sulistyorini (Department of Islamic Education Management, 2025)
Islamic education leadership is very important in shaping the character of students and making quality Islamic education. However, in the current millennial era, there is a shift from traditional Islamic educational leadership to modern Islamic educational leadership. This shift raises several problems that need to be considered by leaders of Islamic education. The method used is a qualitative literature method, namely data collection with literature (research libraries). This article discusses some of the problems of leadership in traditional and modern Islamic education in the millennial era, including differences in the concept of leadership, challenges in using technology, changing values and norms in society, and challenges in maintaining Islamic values amidst the increasingly strong influence of Western culture. The author hopes that this article can provide a clear picture of the problems of Islamic education leadership in the millennial era and help Islamic education leaders overcome these challenges.